2017
DOI: 10.1016/j.epsl.2017.06.052
|View full text |Cite
|
Sign up to set email alerts
|

The ruthenium isotopic composition of the oceanic mantle

Abstract: The approximately chondritic relative, and comparatively high absolute m antle abundances of the highly siderophile elem ents (HSE), suggest that their concentrations in the bulk silicate Earth were primarily established during a final ~0.5 to 1% of "late accretion" to the mantle, following the cessation of core segregation. Consequently, the isotopic composition of the HSE Ru in the mantle reflects an amalgamation of the isotopic compositions of late accretionary contributions to the silicate portion of the E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 47 publications
(75 reference statements)
1
22
0
Order By: Relevance
“…The reported data were reduced using one of two different reduction protocols. One protocol utilized an assumed oxygen isotopic composition (obtained from Nier, 1950) for oxide interference corrections, while the other protocol relied on the direct measurement of the oxygen isotopic composition ("Nier reduction method" and "measured oxygen reduction method", respectively; Walker, 2012; Bermingham et al, 2016;Worsham et al, 2016b;Bermingham and Walker, 2017). The latter reduction scheme became available approximately mid-way through the course of this study with the addition of 10 12 ohm and 10 13 ohm resistor amplifiers to the Triton Plus.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reported data were reduced using one of two different reduction protocols. One protocol utilized an assumed oxygen isotopic composition (obtained from Nier, 1950) for oxide interference corrections, while the other protocol relied on the direct measurement of the oxygen isotopic composition ("Nier reduction method" and "measured oxygen reduction method", respectively; Walker, 2012; Bermingham et al, 2016;Worsham et al, 2016b;Bermingham and Walker, 2017). The latter reduction scheme became available approximately mid-way through the course of this study with the addition of 10 12 ohm and 10 13 ohm resistor amplifiers to the Triton Plus.…”
Section: Methodsmentioning
confidence: 99%
“…To assess the Ru isotope composition of the Earth's mantle, Fischer-Gödde et al 2015reported the Ru isotope composition of a terrestrial chromitite from the Shetland Ophiolite Complex. Subsequently, Bermingham and Walker (2017) reported an estimate of the Ru isotopic composition of the oceanic mantle, which is likely representative of the BSE, from measurements of thirteen different ophiolite chromitites and Os-Ir-Ru alloy grains which sample eight different, mainly Phanerozoic, mantle domains ( Table SM1b). The isotopic compositions of these materials were found to be identical, within analytical uncertainties, to a reference material solution used as a standard in studies of meteoritic Ru.…”
Section: Samplesmentioning
confidence: 99%
“…, Rizo et al . , Bermingham and Walker , Dickson , Mundl et al . ) and extra‐terrestrial (e.g., Akram and Schönbächler , Hunt et al .…”
mentioning
confidence: 99%
“…The relative abundances of NM seen in Figure 1b imply enstatite-like chondrites to be carriers of these species and thus a principal component of the late veneer. Study of the nucleosynthetic isotope anomalies showed a minimal difference between these meteorites and terrestrial rocks: the late veneer was derived from the inner Solar system material with a slightly higher contribution of the s-process nuclides compared with E-chondrites [Bermingham and Walker, 2017;Burkhardt et al, 2016;Fischer-Gödde and Kleine, 2017]. Ruthenium presents a clear isotopic evidence for an inner Solar System origin of the late veneer (Figure 2).…”
Section: Noble Metal Abundances In the Mantlementioning
confidence: 99%